Posterior and anterior tilt increases the risk of failure after internal fixation of Garden I and II femoral neck fracture. (2nd November 2019) - Sjöholm, Pontus; Otten, Volker; Wolf, Olof; Gordon, Max; Karsten, Gustav; Sköldenberg, Olof; Mukka, Sebastian
Abstract : Background and purpose — Preoperative posterior tilt of the femoral head as seen on lateral radiographs has been reported to affect the risk of fixation failure in cases of minimally displaced femoral neck fractures (Garden I–II). We investigated radiological risk factors of treatment failure. Patients and methods — We included 417 patients (68% women, median age: 78 years (50–108) with a minimally displaced femoral neck fracture (Garden I–II) treated with internal fixation in a retrospective cohort study. The patients were followed for 3.4 years (2–14). Data on age, sex, housing, cognitive impairment, implant angulation, pre- and postoperative tilt, hip complications, and reoperations were recorded. The risk of fixation failure was assessed using Cox proportional hazards regression analysis. Results — The overall reoperation rate was 17%, and the rate of treatment failure (fixation failure, nonunion, avascular necrosis, or posttraumatic osteoarthritis) was 13%. Cox proportional hazard analysis revealed an increased risk of treatment failure with a preoperative posterior tilt of at least 20° and a preoperative anterior tilt greater than 10°. A failure occurred in 13 of the 65 patients with a posterior tilt of at least 20° and in 5 of the 9 patients with an anterior tilt greater than 10°. Interpretation — A preoperative posterior tilt of 20° and an anterior tilt greater than 10° in cases of Garden I and II femoral neck fractures increase the risk of fixation failure necessitating additional surgery. In this group of patients, there is a need for future interventional studies regarding the feasibility of primary hip arthroplasty.